Antioxidant-Inspired Drug Discovery: Antitumor Metabolite Is Formed in Situ from a Hydroxycinnamic Acid Derivative upon Free-Radical Scavenging - Fási, Laura; Di Meo, Florent; Kuo, Ching-Ying; Stojkovic Buric, Sonja; Martins, Ana; Kúsz, Norbert; Béni, Zoltán; Dékány, Miklós; Balogh, György Tibor; Pesic, Milica; Wang, Hui-Chun; Trouillas, Patrick; et al. (Journal of medicinal chemistry, 2019)
Cancer cells generally possess higher levels of reactive oxygen species than normal cells, and this can serve as a possible therapeutic target. In this proof-of-concept study, an antioxidant-inspired drug discovery strategy was evaluated using a hydroxycinnamic acid derivative. The processing of oxidized mixtures of p-coumaric acid methyl ester (pcm) revealed a new antitumor lead, graviquinone. Graviquinone bypassed ABCB1-mediated resistance, induced DNA damage in lung carcinoma cells but exerted DNA protective activity in normal keratinocytes, and modulated DNA damage response in MCF-7 cells. The cytotoxic effect of pcm in MCF-7 cells was potentiated under H2O2-induced oxidative stress, and the formation of graviquinone was confirmed by Fenton's reaction on pcm. In silico density functional theory calculations suggested graviquinone as a kinetic product of pcm-scavenging •OH radicals. Our results demonstrate the pharmacological value of an in situ-formed, oxidative stress-related metabolite of an antioxidant. This might be of particular importance for designing new strategies for antioxidant-based drug discovery.
Keywords: signální transdukce; Signal Transduction; kyseliny kumarové; Humans; Computer Simulation; oxidace-redukce; Antineoplastic Agents; Cyclohexanones; lidé; chemorezistence; zvířata; myši; scavengery volných radikálů; Mice; Free Radical Scavengers; objevování léků; počítačová simulace; hydroxylový radikál; Hydroxyl Radical; cyklohexanony; nádorové buněčné linie; protinádorové látky; Oxidation-Reduction; poškození DNA; DNA Damage; Animals; Cell Line, Tumor; Drug Discovery; Coumaric Acids; Drug Resistance, Neoplasm